INNOVATIVENESS OF THE UKRAINIAN ECONOMY ON THE WAY TO THE EU - А.О. ZADOIA (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
The article is devoted to the assessment of the level of innovativeness of the Ukrainian economy in comparison with the innovativeness of the economies of the European Union countries based on the Global Innovation Index 2023 and the justification of ways to increase it in the course of advancing to full membership in the EU. In the course of the study, the hypothesis that there is a close connection between the level of the country’s development, which is measured by the GDP per capita indicator in the model, and the absolute value of the global innovation index was confirmed (correlation coefficient is 0.868). However, Ukraine, which belongs to the group with a below-average GDP per capita indicator, is ahead of more than 30 countries with high and above-average GDP per capita indicators according to the Global innovation index. This strengthens the hope that the creation of the necessary conditions for the realization of innovative potential will be able to accelerate economic growth and lead to a significant increase in GDP in the post-war period. The comparison of the global index of innovativeness of Ukraine with the similar indicator of the EU countries carried out in the article showed a certain lag of our country, which arose in recent years, which can be explained by Russian aggression. However, this lag is not fundamental and can be overcome in a short time. Moreover, among the candidate countries for joining the EU, Ukraine ranks among the top three in terms of innovativeness. Therefore, such a lag should not become an obstacle on the way to the EU. A more detailed analysis of individual indicators that form the global index of innovativeness revealed significant heterogeneity of the innovative environment of the Ukrainian economy, because its rating according to these indicators ranges from 1 to 130. Ukraine’s achievements in performance indicators, which are calculated in relation to GDP, are quite good, which once again confirmed the conclusion that there is a disproportion between the potential and actual volumes of production. The biggest lag is recorded in the indicators related to the business environment, its stability and the legal norms that regulate it. A serious problem for Ukraine is the lack of market and organizational infrastructure. These issues should become the object of special attention of the state on the way to the EU.